Differential ovulation responses in nulliparous and multiparous rabbit females: A cannula-mediated study - Viudes-De-Castro, María P.; Marco-Jiménez, Francisco; Vicente, José S. (Elsevier, 2024)
In order to explore a less stressful and hormone-independent insemination method in rabbits, we aimed to evaluate the influence of a new insemination cannula on reproductive performance. Two assays were conducted. In the first, 136 nulliparous and multiparous females were treated with 12.5 IU of eCG to improve their receptivity and divided into four stimulation groups (aGnRHsingle bondControl, Extender, Seminal and Sperm) to test ovulation frequency and rate. The control group received 1 µg of buserelin acetate intramuscularly to induce ovulation. The other groups used a 3D printed cannula to introduce 0.5 ml of extender, undiluted seminal plasma or resuspended sperm into the vagina. After six days, laparoscopy was performed to assess ovulation frequency and rate. Results showed that nulliparous does exhibited higher ovulation frequencies compared to multiparous does, regardless of the stimulation group. In the second assay, reproductive performance (delivery rate and litter size at birth) of 109 females treated with 12.5 IU of eCG to improve their receptivity was studied after insemination with a seminal dose using the 3D printed cannula. Forty-nine of them were induced to ovulate with buserelin acetate as a control. The results confirmed previous findings, as cannula stimulation allowed better delivery rates in receptive nulliparous than multiparous does. Differential response to multiparous does to the physical stimulus of the cannula could be supported by the histological changes and loss of contractile response that occur after multiple births. Litter sizes at birth were similar between experimental groups. In conclusion, the 3D designed cannula showed promising results in nulliparous does in ovulating frequency, and further refinement is needed to enhance its effectiveness, particularly in multiparous rabbits.